2016
DOI: 10.1016/j.zool.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-genotype infections and their complex effect on virulence

Abstract: Multiple infections are common. Although in recent years our understanding of multiple infections has increased significantly, it has also become clear that a diversity of aspects has to be considered to understand the interplay between co-infecting parasite genotypes of the same species and its implications for virulence and epidemiology, resulting in high complexity. Here, we review different interaction mechanisms described for multiple infections ranging from competition to cooperation. We also list factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 131 publications
0
25
0
Order By: Relevance
“…Alternatively, virulence may change to maximize parasite replication and transmission (Anderson and May ; Alizon and Michalakis ; Bose et al. ). If virulence is too high, the host dies too early and parasite replication is low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, virulence may change to maximize parasite replication and transmission (Anderson and May ; Alizon and Michalakis ; Bose et al. ). If virulence is too high, the host dies too early and parasite replication is low.…”
Section: Discussionmentioning
confidence: 99%
“…The altruistic specialization of cell types resulting in increased production efficiency has been shown for other microorganisms including the Bacillus genus (Strassmann et al 2000;Deng et al 2015;van Gestel et al 2015). Alternatively, virulence may change to maximize parasite replication and transmission (Anderson and May 1982;Alizon and Michalakis 2015;Bose et al 2016). If virulence is too high, the host dies too early and parasite replication is low.…”
Section: Discussionmentioning
confidence: 99%
“…The carriage of multiple distinct parasite clones by an individual is reported to enhance the development of multiple strain specific anti-parasite immunity. However, due to an intense intra-host competition, harbouring multiple distinct parasite clones is also implicated in high gametocyte production and emergence of highly virulent and drug resistant parasite strains 32,[39][40][41][42][43] .…”
mentioning
confidence: 99%
“…The result showed that, MOI and gametocyte density account for about 68.1% of the variations in mosquito infection prevalence. These results can be explained by the emergence of highly virulent and infectious parasite strains due to intense intra-host competition and high recombination rates among the distinct infecting clones [45,46,47]. Another plausible explanation for the association between MOI, gametocyte density and mosquito infection prevalence found in this study may be due to a strategic investment by the parasite to maximise either in-host survival or between-host transmission [42,48,49,50] At relatively low MOI, the level of intra-host competition is relatively low and the P. falciparum parasites reduce the conversion rates to enhance asexual replication and in-host survival through a reproductive restraint process.…”
Section: Discussionmentioning
confidence: 99%